Universal principles of art : 100 key concepts for understanding, analyzing, and practicing art - Parks, John A., 1952- (Beverly, MA : Rockport Publishers, 2015)
"A follow-up to Rockport Publishers' best-selling Universal Principles of Design, a new volume will present one hundred principles, fundamental ideas and approaches to making art, that will guide, challenge and inspire any artist to make better, more focused art.Universal Principles of Art serves as a wealth of prompts, hints, insights and roadmaps that will open a world of possibilities and provide invaluable keys to both understanding art works and generating new ones. Respected artist John A. Parks will explore principles that involve both techniques and concepts in art-making, covering everything from the idea of beauty to glazing techniques to geometric ideas in composition to minimalist ideology. Techniques are simple, direct and easily followed by any artist at any level. This incredibly detailed reference book is the standard for artists, historians, educators, professionals and students who seek to broaden and improve their art expertise"--
Keywords: Art -- Dictionaries; ART / Reference; Art; Dictionaries